Booking System and Procedures for UTHM House Rental Application in Parit Raja - Muhammad Imran Fazli; Munirah Mohd Yusof (Applied Information Technology And Computer Science, 2023)
UTHM House Rental Application (UTHM HRApp) is a mobile-based application that will act as a third-party software mainly to help ease the business processes of students making rent in Parit Raja. The project will adapt with throwaway prototyping methodology. The application is an initiative for Kolej Kediaman Luar Kampus (KKLK) to oversee Pelajar Tanpa Asrama (PTA) students more conveniently and provide them with necessary rent records as a reference for future usage. The application will cover house rents inside the proximity of the Parit Raja area only. The application will be designed using an object-oriented approach. The app will be developed by using Flutter Technology. It uses dart language as the main programming language. Firebase is considered to be the database handler for this project. It is with high hopes that the UTHM HRApp will be used by students to have a better experience renting houses in Parit Raja.